Effect of plastic mulches on growth and yield of potato (Solanum tuberosum L.) in Dadeldhura, Nepal - Bhatta, Manoj; Shrestha, Bhimsen; Devkota, Ananta Raj; Joshi, Khem Raj; Bhattarai, Sabin; Dhakal, Umisha (Journal of Agriculture and Natural Resources, 2020)
A field experiment was conducted from February to June, 2020 at Bhatkanda, Dadeldhura, Nepal to assess the effectiveness of plastic mulches in potato production. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications comprising of five treatments viz: T1: white plastic mulch (white on black colored), T2: silver plastic mulch (silver on black colored), T3: perforated black plastic mulch, T4: black plastic mulch and T5: control (without mulch). Results revealed that the black plastic mulch significantly increased the rate of emergence while perforated black plastic exhibited highest values of all other studied growth parameters, yield components and quality parameters. The highest marketable tuber yield was obtained in perforated black plastic (6.05 kg/m2) followed by silver plastic (5.62 kg/m2), white plastic (5.46 kg/m2), black plastic (5.14 kg/m2) and lowest marketable tuber yield was obtained in control condition (4.07 kg/m2). Similarly, temperature difference between controlled and mulched condition at 15 cm depth of soil was observed up to 2.8°C with its highest value in black plastic mulch and lowest in control condition. The perforated black plastic mulch was found most economical with maximum value of net return (NRs. 1904.31 thousands/ha) and B: C ratio (5.83). This study concludes that the use of perforated black plastic mulch is most economical with optimum plant growth and yield, producing best quality potatoes under climatic condition of Dadeldhura, Nepal.